Amplicon sequencing as a potential surveillance tool for complexity of infection and drug resistance markers in Plasmodium falciparum asymptomatic infections - Wamae, K; Kimenyi, KM; Osoti, V; de Laurent, ZR; Ndwiga, L; Kharabora, O; Hathaway, NJ; Bailey, JA; Juliano, JJ; Bejon, P; Ochola-Oyier, LI (Oxford University Press, 2022)
Background. Genotyping Plasmodium falciparum subpopulations in malaria infections is an important aspect of malaria molecular epidemiology to understand within-host diversity and the frequency of drug resistance markers.